Influence of the trailing edge shape on the aerodynamic characteristics of an airfoil at low Re number using RANS - R. Perrin; P. Rattanasiri; E. Lamballais; S. Yooyen (My University, 2020)
Abstract Recent studies have demonstrated that periodic spanwise modifications of the Trailing Edge of an airfoil can significantly reduce the noise produced and can also increase its aerodynamic performances. This study aims to analyse the effects of such modifications on the aerodynamic performances of a profile by numerical simulation, with a particular emphasis on low Reynolds numbers typical of Unmanned Aerial Vehicles, Micro Aerial Vehicle, and/or small wind turbines. In the range of Re numbers considered here, the flow presents laminar separation eventually followed by transition and reattachment (depending on Reynolds number, Angle of Attack and Free Stream Turbulence). As the standard for industrial applications is still the RANS approach, thanks to its moderate computational cost, this approach is considered here and a first step consists in evaluating the ability of recently proposed transition models (Menter, 2015; Ge, 2014; Kubacki, 2016) to predict the characteristics of the flow for such geometries. A baseline NACA0012 profile is considered, together with modified Trailing Edges (blunt and serrated). Simulations are performed using Code_Saturne (2 nd order finite volume), and the influence of the Free Stream Turbulence, Angle of Attack, and Reynolds number on the aerodynamics performances is examined. The results are compared with data from the literature.
Keywords: Trailing edge; Leading edge; Fluid Dynamics and Turbulent Flows